"We're just building!": a study of collaborative coaching interactions. Issue 3 (29th April 2020) - LeeKeenan, Kira
Abstract : Purpose: This paper aims to clarify opportunities for collaborative interactions between cooperating teachers (CTs) and preservice teachers (PTs) in practice-based teacher preparation programs (TPPs). The study aimed to explore the discursive moves that facilitate collaboration between one CT and PT. Design/methodology/approach: Grounded in the critical sociocultural theory, this study applied a qualitative microanalytic approach to the study of coaching interactions for the purpose of understanding why and how collaborative discourse developed between a CT and a PT. Findings: This study of discourse moves within collaborative coaching interactions revealed collaborative interactions developed from strategic repositioning of social roles, which created space for authentic problem-posing by both the CT and the PT, and the co-construction of teaching events, which supported more specific planning toward future lessons; and routine and appreciative use of observational data created space for co-construction and co-inquiry. Practical implications: This study illuminated the complex social and discursive dance embedded within collaborative interactions. The findings also suggested that the project of co-constructing curriculum with someone is a powerful and necessary experience for a PT because it is through this co-construction that PTs learn how to design meaningful curriculum and critically reflect on practice. Originality/value: This study offers new understandings around how collaborative talk in educational discourse transpires and why providing opportunities for PTs to take a more active role in their own learning is important.